Adaptive evolution of young gene duplicates in mammals - Han, Mira V.; Demuth, Jeffery P.; McGrath, Casey L.; Casola, Claudio; Hahn, Matthew W.

(untitled) (Genome Research, 2009)
Duplicate genes act as a source of genetic material from which new functions arise. They exist in large numbers in every sequenced eukaryotic genome and may be responsible for many differences in phenotypes between species. However, recent work searching for the targets of positive selection in humans has largely ignored duplicated genes due to complications in orthology assignment. Here we find that a high proportion of young gene duplicates in the human, macaque, mouse, and rat genomes have experienced adaptive natural selection. Approximately 10% of all lineage-specific duplicates show evidence for positive selection on their protein sequences, larger than any reported amount of selection among single-copy genes in these lineages using similar methods. We also find that newly duplicated genes that have been transposed to new chromosomal locations are significantly more likely to have undergone positive selection than the ancestral copy. Human-specific duplicates evolving under adaptive natural selection include a surprising number of genes involved in neuronal and cognitive functions. Our results imply that genome scans for selection that ignore duplicated loci are missing a large fraction of all adaptive substitutions. The results are also in agreement with the classical model of evolution by gene duplication, supporting a common role for neofunctionalization in the long-term maintenance of gene duplicates.